Calvarial Thickness of the Nepalese Dry Skulls - Baral, P; Koirala, S; Bajracharya, S; Jha, CB; Banstola, D; Shrestha, RN (Journal of Institute of Medicine Nepal, 2015)
Introduction: Calvarium of skull comprises frontal,parietal and occipital bone.These bones cap over the brain in cranial cavity. These bones are flat bones having outer and inner tables made up of compact bone. There is cancellous bone called as diploe in between the outer and inner table. The aim was to measure the thickness of calvaria at various points on Nepalese skull and establish Nepalese database of calvarial thickness and also to compare thickness on the right and left side for bilateral points.Methods: Around140 calvaria of dried skull were studied. Thickness of various points on the frontal, parietal and occipital bones that form calvaria were measured with spreading caliper. The inner table, diploe and outer table thickness were measured with vernier caliper.Results: The mean thickness of frontal bone is 5.6 ± 0.8 mm;out of which the outer table 1±0.2mm, the inner table 0.8±0.3mm and the diploe 3.8±0.6mm.The mean thickness of parietal bone is 4.5±0.6 mm; out of which the outer table 0.8±0.2mm, the inner table 0.6±0.2mm and the diploe 3.1±0.4mm. The mean thickness of occipital bone is 8.5±0.7 mm;out of which the outer table 2.2±0.4mm, the inner table 1±0.3mm and the diploe 5.7±0.6mm.There is significant difference in the mean thickness of the frontal, parietal and occipital bone(p